“¿Yo soy tu padre?”: reflexiones sobre la regulación actual de la paternidad extramatrimonial - Ramírez Huaroto, Beatriz May Ling (2018)
The regulation of extramarital parenthood is one of the most important issues of Peruvian family law. After several media cases that evidenced the difficulties that stemmed from the original regulation of the Civil Code, significant changes were made. In 2017, almost 5 years after the last modification, the last reforms were undertaken. The work reviews the evolution of the regulation of the judicial declaration of paternity and review of the challenges.